Intranasal Administration of Hyaluronan as a Further Resource in Olfactory Performance in Multiple Chemical Sensitivity Syndrome. (October 2013) - Alessandrini, M.; Micarelli, A.; Bruno, E.; Ottaviani, F.; Conetta, M.; Cormano, A.; Genovesi, G.
Multiple chemical sensitivity (MCS) is a relatively common clinical diagnosis in western populations and its symptoms (i.e. dysosmia) are mainly triggered by chemical compounds, such as common odorants. The aim of this study was to test the effect of intranasal administration of hyaluronic acid (HA) on odour threshold and related quality of life in MCS syndrome. Two randomized groups of MCS patients received 30 days' administration of either a nasal spray (Ialumar®) containing HA [HA group (HAG); n=29] or only physiological solution [PS group (PG); n=30]. Both groups were investigated using the "Sniffin' Sticks" test (SST) battery, Questionnaire of Olfactory Disorder (QOD) and Zung Anxiety Scale (SAS) before randomization and after treatment. Paired t -test analysis found a statistically significant reduction in odour threshold (OT) and an improvement in QOD and SAS between pre- and post-treatment results only in the HAG. Furthermore, positive correlations were found between the OT reduction, SAS and QOD improvement. Thus, intranasal administration of HA could be suggested as a further well-tolerated resource in alleviating MCS olfactory discomfort.